Dari Keberagaman ke Nilai: Bagaimana ESG Menghubungkan Keberagaman Gender dan Nilai Perusahaan - Candy; Verawati; Suprapto, Yandi (Jurnal Manajemen dan Keuangan, 2025)
This study aims to analyze the effect of gender diversity on firm value with ESG performance as a mediating variable. The research was conducted on 65 manufacturing companies in Indonesia that implement ESG performance and have published audited financial reports from 2019 to 2023. A quantitative method was employed using purposive sampling, and data analysis was conducted using Stata 17. The results show that slot777 gender diversity has a significant effect on firm value through ESG performance as a mediator. Gender diversity has a positive influence on ESG performance, while ESG performance has a negative impact on firm value. These findings highlight the important role of ESG in bridging the relationship between gender diversity and firm value.